Differences in fundamental sitting volleyball skills between functional sport classes: a video analysis method - Esatbeyoglu, F.; Marszalek, J.; MacDonald, K.; Ashcroft, L. (International Journal of Performance Analysis in Sport, 2021)
The aim of this study was to investigate the differences between sitting volleyball (SV) skills and para-athletes` sport classes. Twelve games involving 151 athletes from 11 countries from the Rio 2016 Paralympic Games were chosen and analysed according to the Federation Internationale de Volleyball Observational System. An efficacy coefficient was calculated for seven SV skills: attack hit, serve, block, block of serve, defence, setting and receive. Results showed no differences in any SV skills according to the two sitting volleyball sport classes (P>0.05). Intragroup comparisons revealed that SV skills were not different for both genders in disabled (D) and minimal disabled (MD) sport classes (P>0.05) expect for setting skill was better in female para-athletes in MD sport class than female para-athletes in D sport class (P=0.01). Gender comparison revealed that female para-athletes were better in block (P=0.00) whereas male para-athletes were better in receive (P=0.00) in sport class D. In sport class MD, female para-athletes were better in setting (P=0.01) and block (P=0.02) than male para-athletes. The findings of this article provide new insights to SV classification and can lead to a second phase of biomechanically and technically assessing skills and how they can correlate with SV sport classes.